PERSPEKTIF GIZI DAN UPAYA INOVATIF DALAM PENANGGULANGAN DIABETES MELITUS (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Diabetes Mellitus (DM) is a metabolic disorder caused by many factors. Risk factors for DM include genetic factors, increasing age, lack of physical activity and eating patterns or an unbalanced diet. Research shows that there is a tendency to increase the incidence and prevalence of DM in various parts of the world. In 2015, as many as 415 million adults worldwide had diabetes and it is estimated that by 2040 this will increase to more than 642 million.One form of management focus on DM is nutrition which aims to prevent hyperglycemia so that it can reduce morbidity and mortality. Diet planning is an important component in DM management. Non-compliance with diet management including schedule, amount, and type of food consumed is one of the obstacles to achieving treatment goals. People with DM must follow and comply with the diet management program in accordance with the provisions of the health team so that metabolic conditions are optimally controlled for the successful management of diabetes.One of the management for people with DM to maintain blood sugar levels in the body to remain stable is by regulating the nutrition consumed. All people with DM, especially for people with DM who are obese, must do a diet with calorie restrictions so that the body weight of people with DM reaches the ideal limit. The principle of managing nutrition in people with DM is a balanced diet according to the calorie needs of each individual.Diet modification is an important strategy in meal planning for people with DM. Preparation of a food menu for people with DM should not be done haphazardly. The selected menu must meet nutritional needs because each person with DM has different nutritional needs.Medical Nutrition Therapy (TGM) remains essential for effective diabetes management and successful MNT involves an ongoing process of problem solving, adjustment, and readjustment. Healthy food choices and regular physical activity also improve overall health, an added benefit for people living with chronic illnesses. Even so, the implementation of diet planning seems easy to do, but it turns out that many DM sufferers fail.Many innovative studies have been carried out related to the role of nutrition in the management of diabetes mellitus. These include innovations in food processing techniques, applications that make it easier for diabetic patients to manage their diet, even with a genomic (nutrigenomic) approach that still needs strong scientific evidence. The pathogenesis of DM is not fully understood, but nutritional-gene interactions at different levels, genetic predisposition and dietary factors appear to be involved. Nutritional genomics studies generally focus on dietary patterns according to genetic variation, the role of gene-nutrient interactions, gene-diet-phenotype interactions and diet-induced epigenetic modifications.There are still very broad and large developments in both nutrigenetic and nutrigenomic studies that need to be proven and the translation results into clinical applications which are certainly highly expected.